2015
DOI: 10.2169/internalmedicine.54.3586
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of <i>Cryptococcus laurentii</i> Peritonitis in a Patient on Peritoneal Dialysis

Abstract: A 32-year-old man on peritoneal dialysis (PD) was hospitalized for seven days due to fever. A diagnosis of yeast-like fungal peritonitis was made by Gram staining. The patient was started on intravenous micafungin and oral fluconazole therapy following removal of the PD catheter. A fungal pathogen was isolated from the peritoneal fluid and identified as Cryptococcus species. Based on antifungal susceptibility testing, the treatment was changed to voriconazole and continued for 3 months. A genetic analysis iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…gattii have increased significantly since the 1970s, including in renal dialysis patients. The results of the current study also revealed that non- neoformans / gattii cryptococcal species account for a considerable proportion (approximately 27.8%, 5/18) of the cryptococcal species among renal dialysis patients [ 13 17 ], particularly C. laurentii or C. albidus . This observation is consistent with a recent global review of 44 previously published cases [ 11 ].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…gattii have increased significantly since the 1970s, including in renal dialysis patients. The results of the current study also revealed that non- neoformans / gattii cryptococcal species account for a considerable proportion (approximately 27.8%, 5/18) of the cryptococcal species among renal dialysis patients [ 13 17 ], particularly C. laurentii or C. albidus . This observation is consistent with a recent global review of 44 previously published cases [ 11 ].…”
Section: Discussionsupporting
confidence: 60%
“…Of these articles, 735 were excluded because of duplication and/or an inappropriate content. Nearly all of these pooled cases of cryptococcosis during renal dialysis were single case reports [ 13 27 ]. Among these, 16 cases reported in 15 articles with definitive diagnosis of cryptococcosis were analyzed further.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical presentation of C. laurentii is similar to that of C. neoformans, but the cryptococcal antigen test is often negative (4), and the organism exhibits decreased fluconazole susceptibility (5,6). Therefore, accurate identification of the species is essential for treatment drug selection.…”
mentioning
confidence: 99%